Restoring the Balance : Performing Healing in West Papua. - Courtens, Ien (Brill, 2008)
The study offers an ethnographically rich journey through the variety of healing methods in current Ayfat society: indigenous (obtained during female and male initiation rites), biomedical (the missionary hospital), and Christian (created by ritual healers since the coming of the missionaries). Likewise, the causes ascribed to illness range from sorcery, witchcraft, violation of ancestral or biblical rules, to biomedical conditions, a multiplicity of ways of understanding illness and healing that emerged in the context of religious change. Making choices among the variety of healing performanc.